2023
DOI: 10.1002/ptr.7740
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol has potential anti‐coronavirus disease 2019 (COVID‐19) targets based on bioinformatics analyses and pharmacological effects on endotoxin‐induced cytokine storm

Abstract: COVID‐19 has infected 272 million patients and caused 5.33 million deaths around the world, and it remains the main global threat. Previous studies revealed that Chinese traditional medicine is an effective treatment for COVID‐19 infection. This study aims to reveal the pharmacological effects of kaempferol, which is the active component of Radix Bupleuri and Tripterygii Radix, and potential mechanisms for the treatment of COVID‐19. Here, we employed the bioinformatics methods to filter the anti‐COVID‐19 candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 88 publications
1
9
0
Order By: Relevance
“…Kaempferol may play an important role in the prevention and treatment of COVID-19, according to studies (Khalil et al, 2020;Sun et al, 2023). It has been reported that the traditional Chinese herbal Abbreviations: 3CL pro , 3-chymotrypsin-like protease; ACE2, angiotensin-converting enzyme 2; M pro , main proteinase; NSPs, nonstructural proteins; PLpro, papain-like protease; RdRp, RNA-dependent RNA polymerase; S-Protein, spike protein; TMPRSS2, transmembrane serine protease 2.…”
Section: Kaempferolmentioning
confidence: 99%
See 4 more Smart Citations
“…Kaempferol may play an important role in the prevention and treatment of COVID-19, according to studies (Khalil et al, 2020;Sun et al, 2023). It has been reported that the traditional Chinese herbal Abbreviations: 3CL pro , 3-chymotrypsin-like protease; ACE2, angiotensin-converting enzyme 2; M pro , main proteinase; NSPs, nonstructural proteins; PLpro, papain-like protease; RdRp, RNA-dependent RNA polymerase; S-Protein, spike protein; TMPRSS2, transmembrane serine protease 2.…”
Section: Kaempferolmentioning
confidence: 99%
“…Molecular docking analysis revealed that kaempferol can bind the SARS-CoV-2 protein 5R84 and form a hydrogen bond with the residues, whose free binding energy is less than that of the original ligand (Sun et al, 2023).…”
Section: Kaempferolmentioning
confidence: 99%
See 3 more Smart Citations